Investigation on solar still with integration of solar cooker to enhance productivity: Experimental, exergy, and economic analysis. (February 2023) - Angappan, Ganesh; Pandiaraj, Selvakumar; Alrubaie, Ali Jawad; Muthusamy, Suresh; Said, Zafar; Panchal, Hitesh; Katekar, Vikrant P.; Shoeibi, Shahin; Kabeel, A.E.
Abstract: The use of solar still combined with solar energy applications including photovoltaic modules, solar collectors, and solar heaters can significantly impact the system's productivity. In this paper, the combination of solar still and solar box cooker was considered to increase the system's absorption area and water productivity. In order to bring up the temperature of the saline water, it was circulated between the solar cooker and the solar still. A mirror was used on the solar box cooker to enhance solar intensity into the absorber plate. The solar box cooker increases the system's absorption area and improves the saline water temperature. The outcomes illustrated that the passive solar still (PSS) and active solar still (ASS) produced 3.9 L/m 2 per day and 5.5 L/m 2 per day, respectively. Also, the freshwater production was enhanced by about 41 % by modification in comparison with the PSS. Moreover, the cost per liter for the PSS and ASS were approximately 0.0101 and 0.0091 , respectively. In addition, ASS reduced CO2 emissions by 41 % compared to PSS.